Micrococci and Peptidoglycan Activate TLR2→MyD88→IRAK→TRAF→NIK→IKK→NF-κB Signal Transduction Pathway That Induces Transcription of Interleukin-8 - Wang, Qiuling (American Society for Microbiology, 2001)
This study was done to elucidate the signal transduction pathway of interleukin-8 (IL-8) induction by gram-positive bacteria. Bacteria (micrococci) and peptidoglycan (PGN) induced transcription of IL-8 in HEK293 cells expressing Toll-like receptor 2 (TLR2) and CD14 but not in those expressing TLR1 or TLR4. A mutation within the NF-κB site in the IL-8 promoter abrogated transcriptional induction of IL-8 by the two stimulants. Dominant negative myeloid differentiation protein (MyD88), IL-1 receptor-associated kinase (IRAK), NFκB-inducing kinase (NIK), and IκB kinase (IKK) mutant forms completely inhibited micrococcus- and PGN-induced activation of NF-κB and expression of the gene for IL-8. Induction of NF-κB was partially inhibited by dominant negative tumor necrosis factor receptor-associated kinase 6 (TRAF6) but not TRAF2, whereas induction of IL-8 gene was partially inhibited by both TRAF6 and TRAF2. These data indicate that micrococci and PGN induce TLR2-dependent activation of the gene for IL-8 and that this activation requires MyD88, IRAK, NIK, IKK, and NF-κB and may also utilize TRAF6 and, to a lesser extent, TRAF2.